2008
DOI: 10.1021/jp709912d
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Pyropolymer Used as a Precursor of a Noble-Metal-Free Fuel Cell Cathode Catalyst

Abstract: The partial pyrolysis of hemoglobin yielded the hemoglobin pyropolymer, which is an intermediate substance between a polymer and carbonaceous material. The pyropolymer was formed by the heat treatment of hemoglobin below 600°C. The formation behavior of the pyropolymer was examined by thermogravimetry and differential thermal analysis, and the pyropolymer was characterized by elemental analysis and its 13 C nuclear magnetic resonance spectrum. The pyropolymer formation began around 200°C, and aromatic carbon d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 34 publications
(65 reference statements)
2
46
1
Order By: Relevance
“…However, it is convinced that the formation of several weak endothermal peaks displaying on the DTA curve as well as a weight loss of about 45.2% on the TGA curve might be mainly attribute to the decomposition of various amino acids within the PB. Based on the previous reports, it is anticipated that the carbonized procedure of single bioprotein is accomplished at about 500°C and the internal structure of low-temperature carbon materials absolutely shifts from the aliphatic to the aromatic carbon checked by 13 C NMR spectra [22]. For this reason, here a reasonable speculation is put forward that the formation process of PB pyropolymer will be completed at 500°C.…”
Section: Electrochemical Measurementsmentioning
confidence: 86%
See 2 more Smart Citations
“…However, it is convinced that the formation of several weak endothermal peaks displaying on the DTA curve as well as a weight loss of about 45.2% on the TGA curve might be mainly attribute to the decomposition of various amino acids within the PB. Based on the previous reports, it is anticipated that the carbonized procedure of single bioprotein is accomplished at about 500°C and the internal structure of low-temperature carbon materials absolutely shifts from the aliphatic to the aromatic carbon checked by 13 C NMR spectra [22]. For this reason, here a reasonable speculation is put forward that the formation process of PB pyropolymer will be completed at 500°C.…”
Section: Electrochemical Measurementsmentioning
confidence: 86%
“…It is necessary to investigate the carbonization behavior of various proteins. Maruyama et al [22] reported the two-step carbonization process of hemoglobin from bovine blood in 2008. The substance prepared in the first heat-treatment step was designated as a precursor for the catalyst.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This function should promote the LTWGS reaction at the anode and the DHP reaction at the cathode. In fact, excellent progress has been made on noble-metal-free electrodes for fuel cells, [205][206][207][208] but still high-performance and stable electrodes are based on Pt.…”
Section: Nanostructured Electrocatalystsmentioning
confidence: 99%
“…However, some fundamental researches of M N C are often ignored, such as exploring the structure-performance relationship and revealing the active sites. Jasinski has reported that a N 4 -chelate complex with a non-noble metal could be used to electrochemically reduce oxygen in 1964 [13], and following this many macrocyclic transition-metal compounds including of porphyrins, phthalocyanines, and tetraazaannulenes [14][15][16], have been investigated with respect to ORR activity. It has been widely accepted that active sites of ORR in acid solution are M N x in these catalysts [17][18][19].…”
Section: Introductionmentioning
confidence: 99%